Sub-epidermal Expression of ENHANCER OF TRIPTYCHON AND CAPRICE1 and Its Role in Root Hair Formation Upon Pi Starvation - Rishmawi, Louai; Wolff, Heike; Schrader, Andrea; Hülskamp, Martin (Frontiers in Plant Science, 2018)
Root hair patterning is best studied in Arabidopsis thaliana. A pattern of root hair and non-root hair files is governed by a gene-regulatory network of activators and inhibitors. Under phosphate starvation conditions, extra root hairs are formed in non-root hair positions. This raises the question, whether and how this environmental stimulus is mediated by the known root hair gene network. In this study, we provide genetic and molecular data on the role of ETC1 in the phosphate starvation induced ectopic root hair formation. We show that the expression in the epidermis is irregular and reduced and that a new expression domain is induced in the sub-epidermis. By expressing ETC1 in the sub-epidermis, we show that this is sufficient to induce extra root hair formation in N-files. This suggests that the phosphate induced expressional switch from epidermal to epidermal plus sub-epidermal expression of ETC1 is one environmental input to the underlying patterning network.